2011
DOI: 10.2340/16501977-0873
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of falling among stroke patients in rehabilitation

Abstract: Several assessments and both prediction models showed acceptable accuracy in identifying fall-prone patients. A purely physical model can be used; however, looking beyond mobility aspects adds value. Further validation of these results is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 19 publications
3
72
1
2
Order By: Relevance
“…Although it has been previously reported by other authors, factors such as age, gender and polypharmacy, which are often associated with the risk of falls in both healthy elderly and patients with stroke [31][32][33][34][35], were not significant predictors in this study.…”
Section: Discussioncontrasting
confidence: 75%
“…Although it has been previously reported by other authors, factors such as age, gender and polypharmacy, which are often associated with the risk of falls in both healthy elderly and patients with stroke [31][32][33][34][35], were not significant predictors in this study.…”
Section: Discussioncontrasting
confidence: 75%
“…They had been included in an extensive study on risk factors for falling (NZ73). 5 For this gait analysis study, patients had to be able to walk without manual help, with or without walking assistive devices (FAC score !3) and did not have aphasia or dysarthria interfering with verbal tasks (nZ38). Figure 1 illustrates the study design and dropouts.…”
Section: Methods Participantsmentioning
confidence: 99%
“…To avoid (quasi-)empty categories, FAC scores of 4 and 5 were combined in 1 functional category, as previously described. 5 Comparisons between Fs and NFs showed that Fs more frequently used a walking aid (PZ.039) and more frequently were defined as walkers in need of supervision for safety (FAC score of 3) (PZ.044). No significant differences between SFs and MFs were found.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review summarised falls-prediction models derived within the first year after stroke [6]. Five studies derived nine models to predict falls in community-dwellers [7][8][9][10][11]. Three of these studies reported sufficient information to allow for model validation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%